2012
DOI: 10.3892/ol.2012.666
|View full text |Cite
|
Sign up to set email alerts
|

Mutation status of epidermal growth factor receptor and clinical features of patients with combined small cell lung cancer who received surgical treatment

Abstract: Abstract. The mutation status of epidermal growth factor receptor (EGFR) is correlated with the response of tumors to EGFR tyrosine kinase inhibitors in non-small cell lung cancer (NSCLC), suggesting its usefulness as a biomarker in NSCLC. The incidence of EGFR mutation in NSCLC is higher in China than in the United States and European countries. There have been some case reports concerning cases of gefitinib-responsive small cell lung cancer (SCLC) with EGFR mutations. However, few large studies concerning th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
(20 reference statements)
1
23
1
Order By: Relevance
“…In addition, we list five reports which described the EGFR mutation status in resected specimens with combinations of SCLC and adenocarcinoma. [7][8][9][10][11] Fifteen patients were extracted. They also had received no chemotherapy, target therapy, or radiation therapy prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we list five reports which described the EGFR mutation status in resected specimens with combinations of SCLC and adenocarcinoma. [7][8][9][10][11] Fifteen patients were extracted. They also had received no chemotherapy, target therapy, or radiation therapy prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated C-SCLC, and more research should be conducted to identify the clinical features of these patients. 13 Some studies have indicated that the clinical characteristics of C-SCLC patients do not significantly differ from those of pure SCLC patients. 6,8,14 Consistent with this, we found no significant differences in the clinical characteristics between SCLC and C-SCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 Our previous study has shown that epidermal growth factor receptor (EGFR) mutations may occur in C-SCLC, particularly when the "combined" component is adenocarcinoma. 13 More effective treatments (e.g., EGFR-tyrosine kinaseinhibitors) can be administered to patients who have SCLC combined with adenocarcinoma if a definite diagnosis is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…A phase-2 trial of gefitinib in patients with chemosensi tive and chemorefractory relapsed SCLC failed to show any benefit from the use of gefitinib [8]. The EG-FR mutation is rare in SCLC and mainly occurs in combined SCLC or female non-smoker patients [9][10][11][12][13]. A phase-2 trial of imatinib (ST1571) in relapsed SCLC patients with expression of the c-kit gene reported negative results [13].…”
mentioning
confidence: 99%
“…The EG-FR mutation is rare in SCLC and mainly occurs in combined SCLC or female non-smoker patients [9][10][11][12][13]. A phase-2 trial of imatinib (ST1571) in relapsed SCLC patients with expression of the c-kit gene reported negative results [13]. A pyrosequencing assay was used to detect mutations in c-kit exons 9 and 11 in 36 SCLC patients who underwent surgical treatment at the Zhejiang Cancer Hospital, Hangzhou, China, between 1998 and 2010; no mutations in c-kit exons 9 and 11 were detected [15].…”
mentioning
confidence: 99%